PENGARUH GCG TERHADAP KUALITAS LABA DAN DAMPAKNYA PADA BIAYA EKUITAS PADA PERUSAHAAN BARANG KONSUMSI - Zabrina, Avissa; Jacobus Widiatmoko (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Good earnings quality and being able to minimize the cost of equity are the goals of the company. This study aims to analyze the effect of Good Corporate Governance consisting of the board of commissioners, audit committee, audit quality and managerial ownership on earnings quality and to examine the effect of earnings quality on the cost of equity with leverage, firm size and market to book ratio as control variables. The object of this research is the goods and consumption sector companies listed on the Indonesia Stock Exchange in 2015-2020. Tests conducted using multiple regression analysis test. The results showed that GCG as proxied by the board of commissioners and managerial ownership had a significant positive effect on earnings quality, while audit committees and audit quality had no effect on earnings quality. Earnings quality has a positive effect on the cost of equity. Leverage and market to book ratio are not control variables of earnings quality on the cost of equity, while firm size can act as a control variable for earnings quality on the cost of equity with firm size having a positive effect on the cost of equity